The Effects of Fast Food on Healthy Among Malaysian University Students - Yang, Liu (2013)
Fast food industry based on its advantages which continually innovation in order to meet the requirements of different customer groups. The main advantages include good taste, convenience, low price, environment and others which bring a lot of benefits for customer. But fast food also bring some problems at the same time, so the author would like to do this research, to identify the impact of fast food on healthy among Malaysia university students, because the author is a university student and like to eat fast food very much, the author would like to learn deeply about fast food industry and share the result for everyone. The quantitative survey was completed by 200 students from five universities in Kuala Lumpur. Actually it is very difficult to collected data because the author is international student which does not have experience to communicate closely with local people, but the author choose the survey universities which also have international students from China and ask them for help and finally the author completed received 200 sets of questionnaires and finished the research. The author treated this research very carefully and paid fully attention to do every part of it, the author personally agree that the overall research is worth to read it.